Legal Evolution: Analyzing Minerba Law No. 3/2020 Amendments on Reclamation and Post-Mining Responsibilities: Evolusi Hukum: Menganalisis UU Minerba No. 3/2020 Perubahan atas Reklamasi dan Tanggung Jawab Pascatambang - Lestari, Melati Indah; Rosnawati, Emy (Universitas Muhammadiyah Sidoarjo, 2024)
This study analyzes shifting norms in Indonesian mining law, focusing on the phrases